(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2025)
Both industrial development and commercial bank-provided financial services show direct correlation with each other in today’s world. There exists an acknowledged need for bank financing in industrial development yet research on bank services dedicated to this sector remains scarce particularly within emerging markets. The research addresses this knowledge deficit by studying banking services which support industrial financing from both the availability and practicality and user accessibility aspects. The research used a combination of qualitative bank official and industrial stakeholder interviews along with quantitative bank financial data analysis spanning five years. The research shows commercial banks utilize credits, equipment financing and project loans as financial tools yet industrial firms encounter difficulties due to operational red tape and mandatory guarantees together with restricted risk mitigation methods. The results indicate that existing financial products do not meet the genuine needs of production enterprises that focus mainly on small and medium manufacturing operations. The study demonstrates that banking services need specific adjustments to create improved industrial productivity together with economic resilience. Policy reforms should target three main areas by removing financial obstacles and improving educational skills about finances and creating private-public sector connections to make banking services support industrial economic objectives better.